Библейские сказания: сказания евангелистов : [перевод с польского] / З. Косидовский - Косидовский Зенон (Политиздат, 1990)
Экземпляры: ЧЗ (20151225) / Инвентарный номер: 28436 / Цена: 5.00 / Сис.шифр: 86.37 / Авт.знак: К71 / ГРНТИ: 21 / ББК: 86.37